Exploring Textuality and Reader Orientation: Unveiling Interpretative Tendencies in Understanding Nafs Wahidah in QS. Al-Nisa of the Qur'an - Ghozali, Mahbub; Nadia, Matsna Afwi (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
The identification of the meaning of nafs wāḥidah, as produced by various interpretations through Adam, is claimed to be a biased interpretation mechanism based on certain orientations. This research aims to uncover the interpreters' orientation towards the text by situating the interpretation process as the interpreter's interaction with the text within a specific communication context. To achieve this objective, a qualitative method is employed in this research, utilizing a reception frame introduced by Wolfgang Iser. This study reveals that the interpreter's orientation towards specific meanings is constrained by the linguistic structure of the Qur'an, which has been schematized. This constraint on the interpreter's orientation occurs when seeking the contextual significance of the verse through syntagmatic and paradigmatic interconnections. The interpreter's relationship with the Qur'an within a specific communication context limits and shapes tendencies in the interpretation process, which is text-driven. In this context, the interpretation of the term nafs wāḥidah, in its various forms, does not exhibit any discernible biases towards producing meanings in alignment with the interpreter's preferences. Instead, the interpreter solely seeks contextual clues within the verse's structure, thereby associating the meaning of nafs wāḥidah with other terms in an interconnected context.